MODEL PENDIDIKAN NILAI ISLAM BERBASIS DI GAMPONG LIEUE, KECAMATAN DARUSSALAM, KABUPATEN ACEH BESAR - Ilham, Ilham; Jasmadi, Jasmadi; Winarty, Asih; Ismail, Muhammad Nasir (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
The phenomenon of a crisis in manners affecting today's youth is a complex and urgent issue, especially with the massive wave of digitalization. Gampong Lieue, as one of the religious communities in the Darussalam District of Aceh Besar, isn't immune to this challenge. This research talks about how a community-based Islamic values education model can be a solution to tackle this decline in manners. The problems raised depart from the weak appreciation of Islamic values in the social interaction of the community, especially in the younger generation, which is characterized by an increase in deviant behavior, low manners, and a weakening of respect for parents and community leaders. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, participatory observations, and documentation studies of religious leaders, parents, teachers, and local youth. The results of the study show that the Islamic value education model that involves the active role of the community, namely gampong recitation, ta'lim assembly, and the example of community leaders, is able to reshape collective consciousness and instill adab values in a contextual and sustainable manner. This study recommends strengthening collaboration between formal institutions (schools), families, and customary institutions in strengthening the community-based Islamic value education ecosystem, as well as the integration of the adab curriculum in every socio-religious activity of the community in the digital era